A photochemical route to ferrocenyl‐substituted ferrapyrrolinone complexes. (5th May 2017) - Jha, Badri Nath; Raghuvanshi, Abhinav; Joshi, Raj Kumar; Mobin, Shaikh M.; Mathur, Pradeep
Abstract : In the presence of iron pentacarbonyl, photochemical reaction between phenylisocyanate and ferrocenylacetylene results in ferrapyrrolinone complex [Fe2 (CO)6 (μ2 ‐η 3 ‐FcC═C(H)C(O)NPh)] (1 ) and maleimide 3‐ferrocenyl‐1‐phenyl‐1 H ‐pyrrole‐2, 5‐dione (2 ). Under similar experimental conditions, ferrocenyl−/phenyl‐substituted butadiyne primarily shows the activation of only one C☰C bond and results in ferrapyrrolinone complexes [Fe2 (CO)6 (μ2 ‐η 3 ‐FcC═C(C☰CR)C(O)NPh)] (3, R = Fc; 3a, R = Ph), maleimides 3‐ferrocenyl‐1‐phenyl‐4‐(ferrocenylethynyl)‐1 H –pyrrole‐2, 5‐dione (5 ) and 3‐ferrocenyl‐1‐phenyl‐4‐(phenylethynyl)‐1 H –pyrrole‐2, 5‐dione (5a ) and [Fe2 (CO)6 (μ2 ‐η 3 ‐FcC═C(R)C(O)NPh)] (4 ; R = 3‐ferrocenyl‐1‐phenyl‐1 H ‐pyrrole‐2, 5‐dione). Compound 4 consists of ferrapyrrolinone and a maleimide unit, formed by the activation of both C☰C bonds of diferrocenylbutadiyne. Activation of both C☰C bonds in a substituted butadiyne is a rare observation. Formation of the ferrapyrrolinone compounds is an advance over the earlier reported methods which generally use internal alkynes and involve prior synthesis of other clusters. Abstract : Phenylisocyanate with bi‐substituted butadiyneacetylene or ferrocenylacetylene gives ferrapyrrolinone complexes in the presence of iron pentacarbonyl under photolytic conditions. Ferrapyrrolinone complex transforms into maleimide. Reaction also shows a rare activation of both the C ≡ C bonds of diferrocenylbutadiyne.